The Effect of On The Job Training on Problem Solving Skills and Self Efficacy of Aviation Polytechnic Cadets - Setiyo; Andayani, Thursina; Febiyanti, Herlina; Eska Nugraha, Minulya (Langit Biru: Jurnal Ilmiah Aviasi, 2024)
Aviation Polytechnic is a vocational education that should follow the global vocational education. The Polytechnic prepares its graduates not only to achieve education but also to develop social attitudes and skills in various fields. On-the-job training (OJT) programs were then conducted to increase some of these skills, namely problem-solving and self-efficacy (confidence in their abilities). This study aimed to determine whether OJT affected problem-solving skills, self-efficacy, and both. It used a quantitative method with a questionnaire as the instrument for data collection. The data were analyzed by a series of tests that examined the instrument, the prerequisite test, and the hypothesis. They were examined using the MANOVA method. The study indicated that OJT affected the problem-solving skills of Palembang Aviation Polytechnic cadets. The study also found the effect of OJT on the cadets’ self-efficacy. Finally, it was found that OJT had an effect on both problem-solving skills and self-efficacy.